Evaluation of diagnostic methods for detection of trichomoniasis in symptomatic women with vaginal discharge - Gargee Mishra; Kavita Gupta; Srujana Mohanty; Subarna Mitra; Arvind Kumar Singh (Journal of Infection in Developing Countries)
Introduction: Vaginal discharge is a common gynecological condition among reproductive age women. Common infections include bacterial vaginosis (BV), vulvovaginal candidiasis (VVC), and trichomoniasis. Prevalence of trichomoniasis varies with geographical area and the diagnostic techniques used. This study was conducted to compare various diagnostic methods for detection of trichomoniasis among women of the reproductive age group.